Intelligence, Subterfuge and History: A Note on the Vickery-Ubonsri Fragment - Baker, Chris; Pasuk Phongpaichit (The Journal of the Siam Society, 2021)
The document that Michael Vickery and Ubonsri Atthaphan discovered in the 1970s, which was called a “Fragment” (ฉะบับปลีก, chabap plik), is different from other Siamese historical texts in both form and content. It suggests that early Ayutthaya had a network of intelligence gathering and espionage, and that history in the making was recorded in some detail.